Ultra-capacitor based Hybrid Electric Vehicle (Medium) for Developing Countries - Md. Zahid Hasan; Md. Rubaiat Adnan; Sabhasachi Saha; Souvik Roy (Dept. of Chemical Engineering, Diponegoro University, 2018)
This research is directed to the hybridization of battery and ultra-capacitor for a better effectiveness. This portrays the benefits of introducing an ultra-capacitor into a battery pack of an urban electric vehicle drive train. Matlab Simulations are done taking two basic scenarios into consideration: fresh cells and half-used battery cells. The simulations show that the lower the temperature (25-28 OC) higher the hybrid system efficiency (25-30%). Data from real world and previous studies are considered to conduct this study. Previous studies showed efficiency raise upto 7%, whereas this system showed around 14% efficiency raise. Simulations are done considering modified Bangladeshi drive cycle for low weight vehicles. Several issues like volumetric, gravimetric and cost issues of hybridization are present in this paper. By this system the power loss of the system can be reduced by up to 5% to 10% regarding to conventional system. Finally hybridization not only increases the efficiency of the energy storage system also increases the power train efficiency and battery lifespan. This paper would help researchers for further development of this topic.